SPE/DOE Enhanced Oil Recovery Symposium 1992
DOI: 10.2118/24143-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a South Louisiana CO2 Huff ’n’ Puff Field Test

Abstract: SPE Members Abstract A DOE-sponsored field test of the cycle CO2 injection process was conducted by members of Louisiana State University's Petroleum Engineering Department in conjunction with an independent operator. The test well was the Frank J. Bollich, et al. No. 5, located in Acadia Parish, Louisiana, and operated by Southwest Gas Producing, Inc. The well was drilled in December, 1987, and completed in the 4500 ft. Channel Sand of the Bayou Mallet Field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…A greater permeability caused by carbonic acid dissolution of calcium carbonate has been well documented (Torabi and Asghari 2010). Schenewerk et al (1992) performed a study in South Louisiana and showed that CO 2 huff-n-puff can significantly reduce the water cut in wells and alter the saturation distribution. Besides, the diffusion coefficient of CO 2 in oil is higher than nitrogen and water (Zheng and Yang 2017;Zhu et al 2018c), and the adsorptive properties of CO 2 in kerogen are greater than those of other gases (Mitchell et al 2004;Kurniawan et al 2006;Ottiger et al 2008;Pollastro et al 2008).…”
Section: Introductionmentioning
confidence: 91%
“…A greater permeability caused by carbonic acid dissolution of calcium carbonate has been well documented (Torabi and Asghari 2010). Schenewerk et al (1992) performed a study in South Louisiana and showed that CO 2 huff-n-puff can significantly reduce the water cut in wells and alter the saturation distribution. Besides, the diffusion coefficient of CO 2 in oil is higher than nitrogen and water (Zheng and Yang 2017;Zhu et al 2018c), and the adsorptive properties of CO 2 in kerogen are greater than those of other gases (Mitchell et al 2004;Kurniawan et al 2006;Ottiger et al 2008;Pollastro et al 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Значительное влияние на эффективность технологии СО 2 Huff-n-Puff оказывает оценка корреляции технологических параметров, характеризующихся временными интервалами закачки и добычи. Выявление точных математических зависимостей нефтеотдачи от количества циклов, времени закачки, выдержки и до-бычи позволит добиться максимального эффекта от проведения технологии СО 2 Huff-n-Puff [14][15][16][17][18].…”
Section: режимные технологические параметрыunclassified
“…Huff 'n' puff includes the cyclic injection of CO 2 into the reservoir, which after a "soaking" period is put back into production. This low cost technique was widely investigated and showed great potential for EOR both in laboratory and field tests [6][7][8][9][10]. The other approach, called CO 2 -WAG (Water Alternating Gas), uses periods of CO 2 injection followed by water, displacing remaining oil and supporting reservoir pressure.…”
Section: Introductionmentioning
confidence: 99%